PEMANFAATAN BADAN JALAN BAGI PEDAGANG KAKI LIMA DI SEPANJANG JALAN HR. SOEBRANTAS KECAMATAN TAMPAN KOTA PEKANBARU - Bestari "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted along Jalan Hr. Soebrantas from the intersection of the four red lights Pasar Pagi Arengka to the Garuda Sakti intersection, where the road is used by the community to carry out their daily activities but the condition of this road is not as expected. The number of street vendors who trade on the road so that traffic jams often occur and disrupt traffic lanes, it is clear in Regional Regulation No. 05 of 2002 concerning public order, that public areas are not justified as places to store goods or to sell because they can disrupt traffic flow and damage the beauty of the city. . Therefore, researchers are very interested in this problem. Do street vendors understand or know the rules for prohibiting selling in street vendors in the legislation according to Regional Regulation Number 5 of 2002? What are the factors that cause street vendors to continue selling at that location? How to Implement Regional Regulations (Perda) along Jalan HR. Soebrantas Handsome District, Pekanbaru City? The theory used by the researcher is Instrumental Rational Action by Max Weber where the socio-economic conditions of street vendors carry out work or actions according to their circumstances and abilities to achieve their needs. The purpose of this study is to analyze the causes of street rioters operating on the road. The method used in this research is descriptive quantitative. Data collection techniques are observation, questionnaires and documentation with random sampling technique. The results of the research show that many traders are aware of Perda No. 05 of 2002, but in order to meet the economic needs of street vendors, they violate it. Researchers suggest that the government pay more attention and provide a suitable location for small traders so that there are no more street vendors selling on the road. Keywords: economy; Street Vendors; Perda no 05